2020
DOI: 10.1101/2020.07.01.181818
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defining endogenous TACC3–chTOG–clathrin–GTSE1 interactions at the mitotic spindle using induced relocalization

Abstract: A multiprotein complex containing TACC3, clathrin, and other proteins has been implicated in mitotic spindle stability. To disrupt this complex in an anti-cancer context, we need to understand the composition of the complex and the interactions between complex members and with microtubules. Induced relocalization of proteins in cells is a powerful way to analyze protein-protein interactions and additionally monitoring where and when these interactions occur. We used CRISPR/Cas9 gene-editing to add tand… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Previous microscopy studies suggested that chTOG localizes to kinetochores ( Campbell et al, 2019 ; Gutiérrez-Caballero et al, 2015 ; Ryan et al, 2020 ), similar to the budding yeast ortholog ( Miller et al, 2016 ; Miller et al, 2019 ); however, it was unclear if this population was simply bound to microtubule tips. To address this, we used engineered HCT116 cells where the endogenous chTOG genes were epitope tagged with EGFP ( Cherry et al, 2019 ) to determine whether chTOG specifically localizes to kinetochores throughout mitosis ( Figure 1a ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous microscopy studies suggested that chTOG localizes to kinetochores ( Campbell et al, 2019 ; Gutiérrez-Caballero et al, 2015 ; Ryan et al, 2020 ), similar to the budding yeast ortholog ( Miller et al, 2016 ; Miller et al, 2019 ); however, it was unclear if this population was simply bound to microtubule tips. To address this, we used engineered HCT116 cells where the endogenous chTOG genes were epitope tagged with EGFP ( Cherry et al, 2019 ) to determine whether chTOG specifically localizes to kinetochores throughout mitosis ( Figure 1a ).…”
Section: Resultsmentioning
confidence: 99%
“…Endogenous TACC3 does not appear to phase-separate in mitotic cells, regardless of the presence or absence of centrosomes [98,103,104]. The LISD is thus likely a meiosis-specific mechanism for enriching microtubule regulatory factors within the large cytoplasmic volume of oocytes.…”
Section: Open Accessmentioning
confidence: 92%
“…This research was centered on TACC3, which is a well-recognized member of the TACC family and a centrosome and microtubuleassociated protein [29]. Whereas the function of TACC3 is yet to be comprehensively clarified, cumulative proof from research reports indicates that TACC3 is necessary for attachment of kinetochore-microtubule, assembly of centrosome dependent microtubule, and the alignment of spindledependent chromosome in the process of mitosis [30,31].…”
Section: Discussionmentioning
confidence: 99%